Annual review of the sociology of religion. - Jonveaux, Isabelle.; Pace, Enzo.; Palmisano, Stefania. (Annual Review of the Sociology of Religion, 2014)
In contrast with the growing belief in society that traditional religious institutions are losing credibility, there has been renewed interest in monasteries going beyond what is strictly defined as religious. There are, for example, increasingly numerous requests for cooking and gardening courses as well as guided tours in monasteries, the appeal of monastic products and media interest in the subject. In parallel with a strong crisis in its recruitment, monasticism in the Western world is experiencing a period of innovation and experiments accompanied by unexpected popularity, as is evidenced by numerous films and publications. We hope that this book will deepen the understanding of the specificity of monastic life in the in the contemporary world, in a religious area, and from a sociological point of view.